The Influence Of Product Quality And Word Of Mouth On Customer Loyalty (Survey of tofu factory customers MS Tasikmalaya) - Salsabila, Salsa; Pauzy, Depy Muhamad; Asyiah, Ai Kusmiati (Journal of Law, Social Science, and Management Review, 2024)
The purpose of this research is to determine and analyze the influence of Product Quality and Word of Mouth variables on Customer Loyalty of MS Tasikmalaya Tofu Factory Customers. The research method used was a survey method of data obtained directly through questionnaires to 100 respondents taken from customers of the MS Tasikmalaya Tofu factory. The technique used is multiple linear regression. Based on the results of this research, it is known that there is a significant simultaneous influence between Product Quality and Word of Mouth on Customer Loyalty. Product Quality partially has a significant effect on Customer Loyalty and Word of Mouth Partially has a significant effect on Customer Loyalty of the MS Tasikmalaya Tofu factory.